High Wages, Psychosocial Safety Climate, and Employee Engagement on Millenials - Andi Nasrawati Hamid; Resekiani Mas Bakar; Yani Purnama Yana; St Hadjar Nurul Istiqamah (Universitas Negeri Makassar, 2023)
The demographic bonus gives birth to productive millennials who now occupy the industrial world. However, the characteristics of millennials who are less loyal and less interested in long-term employment encourage companies to think of the right strategies for fostering employee engagement. This study aims to examine the effect of the psychosocial safety climate (PSC) on employee engagement among millennials compared to high salaries. In general, previous PSC research used survey methods with self-reports. PSC studies are still very limited with experimental methods, as well as in the context of Millennial generation research. The research was experimental study. The manipulation is given in the form of a vignette: high PSC-low salary versus low PSC-high salary. Vignettes were given to 65 participants, all millennial job seekers who are not self-employed. The results of the t-test show that Millennials prefer to apply and be involved in companies that prioritize a psychological health climate rather than financial goals (salaries). This study supports the self-determinant theory, especially in millennials, in regards to choosing companies. This research has implications for companies concerning policies, practices, and organizational procedures to protect psychological health and safety, especially for millennials.